Detection and characterization of in-service damage in lattice structures using ultrasonics - Tarar, Hasan (2025)
This thesis investigates the detection, quantification, and localization of in-service damage in additively manufactured lattice structures using ultrasonic techniques. Lattice structures, characterized by their lightweight design and superior strength-to-weight ratio, have gained significant attention across aerospace, automotive, and biomedical industries. However, their intricate geometries and susceptibility to defects during additive manufacturing (AM) and operational use pose critical challenges to ensuring their structural integrity. The research aims to address these challenges by developing a robust methodology for structural health monitoring (SHM) in lattice structures, leveraging advanced ultrasonic testing and machine learning models.